"Concerning Change": the Adoption and Implementation of the New Zealand Bill of Rights Act 1990 - Keith, Kenneth J (Victoria University of Wellington Law Review, 2000)
This article draws on a paper delivered by the author, a Judge of the New Zealand Court of Appeal, to the 10th Anniversary International Conference of the Society for the Reform of Criminal Law, London, 27 July – 1 August 1997. In it, the author comments on the process leading to the enactment of the New Zealand Bill of Rights Act 1990 and its implementation. The origins and basic characteristics of the Act are discussed, and the impact of the Act on the preparation of legislation is explored. The author then considers the impact of the Act on the Courts and raises some important issues and questions regarding the future of the Act.